Relation of Syn-Depositional Faulting with Carbonate Growth using Miocene Carbonate Platforms of Central Luconia Province, Malaysia - SN Fathiyah Jamaludin, Manuel Pubellier, David Menier, . (2014)
Interpretation of two Miocene carbonate platforms in Southeastern part of Central Luconia Province has provided an insight of the structural history of the platforms, relating syndepositional faulting with the platform evolution and it's internal architecture. Six horizons have been interpreted on both platforms.